PENGARUH SELF LEADERSHIP DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA UPTD SERTIFIKASI BENIH DINAS KETAHANAN PANGAN, TANAMAN PANGAN DAN HORTIKULTURA PROVINSI SUMATERA UTARA - Barus, Kania Humaira; Aprinawati; Makmur, Chesa Syaqira (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The aim of this research is to determine the influence of self-leadership and competence on employee performance at the Seed Certification UPTD of the Food Security, Food Crops and Horticulture Service of North Sumatra Province. Data collection methods in this research were interviews, observation and questionnaires. Questionnaires were given to 70 respondents using the side total method. This research used multiple linear regression analysis techniques. The research method used is a quantitative method. Based on the results of the analysis, the conclusion from this research is that self-leadership has a positive and significant effect on employee performance at the Seed Certification UPTD of the Food Security, Food Crops and Horticulture Service of North Sumatra Province. This means that the better self-leadership, the higher the performance of employees at the Seed Certification UPTD of the Food Security, Food Crops and Horticulture Service of North Sumatra Province. Competency has a positive and significant effect on employee performance at the Seed Certification UPTD of the Food Security, Food Crops and Horticulture Service of North Sumatra Province. This means that the better the employee’s competency, the higher the employee’s performance at the Seed Certification UPTD of the North Sumatra Province Food Security, Food Crops and Horticulture Service. Self-leadership and competence simultaneously have a positive and significant effect on employee performance at the Seed Certification UPTD of the Food Security, Food Crops and Horticulture Service of North Sumatra Province.